Information technology skills development for accounting graduates : intervening conditions - Senik, Rosmila; Broad, Martin (Canadian Center of Science and Education, 2011)
This paper discusses the findings on factors perceived to mitigate educators from incorporating IT skills in their taught unit(s). The factors are discussed under three main categories, which are academic staff-based barriers, environmental-based barriers and student-based barriers. These barriers should be considered in order to encourage the integration initiatives and its successful implementation. These findings make significant contribution towards enhancing IT skills development and innovation in accounting education.